Writing the History of Emotions Concepts and Practices, Economies and Politics - Frevert, Ute 1954- (Writing History, 2024)
1 Affects, Passions and Emotions: Historical Experiences and Historiographical Approaches -- Part One Emotional Concepts and Practices -- 2 Trust Talk and Trust Work -- 3 Practising Honour: Social, Gender and Legal Perspectives -- 4 Honour and Shame in International Relations -- 5 Shame and Shaming in Modern History -- 6 Historicizing Empathy -- Part Two Emotional Economies of Capitalism -- 7 Capitalist Cold? Bringing Emotions Back In -- 8 How Does Homo Oeconomicus Cope with Emotions? -- 9 Greed and Avarice: Feelings about Money -- 10 Hans in Luck , or the Emotional Economy of Happiness in the Modern Age -- 11 Emotions and Material Culture: Say It with Flowers -- Part Three Politics of Emotion -- 12 Emotional Politics in Europe's Long Nineteenth Century -- 13 Love and Hate, Faith and Despair under National Socialism -- 14 Emotional Styles and Political Cultures in East and West Germany -- Name Index.